Trajectory-Based Hierarchical Adaptive Forwarding in Vehicular Ad Hoc Networks. (11th January 2017) - Wang, Hao; Chen, Liangyin; Liu, Shijia; Fu, Songtao; Luo, Qian; Yin, Feng; Sun, Limin; Li, Zhanghua
Abstract : This paper proposes a Trajectory-Based Hierarchical Adaptive Forwarding (THAF) scheme, tailored and optimized for the efficient multihop vehicle-to-vehicle (v2v) data delivery in vehicular ad hoc networks. We utilize the trajectories of vehicles provided by GPS-based navigation systems to predict forward delay and access area in a privacy-preserving manner. Different from existing trajectory-based forwarding schemes, we establish a hierarchical VANET topology to optimize forwarding path and adopt adaptive diffusion strategy to forward data in light-traffic situations. Through theoretical analysis and extensive simulation, it is shown that our design performs better than the existing schemes.